A new beamforming-based meg dipole source localization method - Mohseni, H; Sanei, S (2010)
In this study a novel deflation based beamforming (BF) method for multiple dipole source localization of surface magnetoencephalogram (MEG) is considered. Two more constraints are added to the conventional BF formulation and a closed-form solution is given. The first constraint minimizes the power of the noise at the output of the BF. The second constraint simultaneously deflates the identified dipoles and identifies the next dipole. This method is called deflation BF and is capable of detecting highly correlated sources, as well as sources with small power which are dominated by other sources. An iterative deflation and localization method is also proposed to improve the accuracy of the method. The proposed method is compared with conventional BF for both simulated and real MEG data. ©2010 IEEE.